9-Aryl Substituted Hydroxylated Xanthen-3-ones: Synthesis, Structure and Antioxidant Potency Evaluation - Elma Veljović; Selma Špirtović-Halilović; Samija Muratović; Sunčica Roca; Snežana Trifunović; Amar Osmanović; Davorka Završnik; Lidija Valek Žulj (Croatica Chemica Acta, 2015)
Oxidative stress is directly related to several diseases and symptoms, where antioxidant compounds, such as xanthenes, may become important in prevention and/or treatmant. Ten biologically active 9-aryl substituted 2,6,7-trihydroxyxanthen-3-one derivatives were synthesized using reliable one-pot synthesis and their structures were confirmed by IR, 1H and 13C NMR spectroscopy and mass spectrometry. Some of the synthesized compounds were scanned for their antioxidant potency using electrochemical method cyclic voltammetry of immobilized microparticles. Substitution of hydrogen at the phenyl ring of 2,6,7-trihydroxy-9-phenylxanthen-3-one with an electron-donating group affected the reducing power of the compounds by lowering the biological oxidation potential. These results signify the importance of xanthen-3-one derivatives as antioxidant agents and their further biological evaluation.